2020
DOI: 10.1038/s41598-020-61569-z
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community structure and functional properties in permanently and seasonally flooded areas in Poyang Lake

Abstract: Water level fluctuations are an inherent feature regulating the ecological structures and functions of lakes. It is vital to understand the effects of water level fluctuations on bacterial communities and metabolic characteristics in freshwater lakes in a changing world. However, information on the microbial community structure and functional properties in permanently and seasonally flooded areas are lacking. Poyang Lake is a typical seasonal lake linked to the Yangtze River and is significantly affected by wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Shrimp pond farming in Thua Thien Hue Province proceeds over several phases: pond preparation, shrimp fry selection, shrimp rearing management, and post-harvest management (Figures 2a and 2b). Environmental factors shape the structure and function of microbial communities, and research has shown that the succession of microbial communities was influenced by combinations of available organic matter, TN, TP, chemical oxygen demand, pH, and feed sources of the ponds (Alfiansah et al, 2018;Liu et al, 2020). Recently, researchers have studied the impact of pH on the cultured shrimp digestion process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shrimp pond farming in Thua Thien Hue Province proceeds over several phases: pond preparation, shrimp fry selection, shrimp rearing management, and post-harvest management (Figures 2a and 2b). Environmental factors shape the structure and function of microbial communities, and research has shown that the succession of microbial communities was influenced by combinations of available organic matter, TN, TP, chemical oxygen demand, pH, and feed sources of the ponds (Alfiansah et al, 2018;Liu et al, 2020). Recently, researchers have studied the impact of pH on the cultured shrimp digestion process.…”
Section: Resultsmentioning
confidence: 99%
“…Scientists have suggested that shrimps incorporate 24 to 37% of nitrogen and 11 to 20% of phosphorus from the feed into their bodies. The presence of leftovers will result in changes in pH, dissolved oxygen in the water and pond sediment, and the extent of proliferation of bacteria and plankton (Alfiansah et al 2018;Liu et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between species are more frequent and intense in one module than in the rest of the community (Newman, 2006). Therefore, a small disturbance in the main module of a microbial network can have a large effect on the entire network of microbial communities (Liu et al, 2020). Moreover, higher mean degree and high closeness centrality and lower betweenness centrality could be used together to identify bacterial keystone taxa (Banerjee et al, 2018), which were mainly classi ed as Ascomycota, Actinobacteria and Proteobacteria in both networks.…”
Section: Co-occurrence Network Of Microbial Communitymentioning
confidence: 99%
“…Microorganisms are sensitive to environmental changes and play an important role in soil carbon fixation in wetlands. Previous studies have revealed that the soil microbial community in the Poyang Lake wetland changed with variations in the water level [19] and vegetation [20]. However, to date, no comparative research on the effects of water level and vegetation type on soil microbial community in Poyang Lake wetland has been conducted.…”
Section: Introductionmentioning
confidence: 99%